Plant density and pruning effects on leaf production of Morus alba cultivars - Rúbia, Antonio Castilho; Sobrinho, João Aloisi; Abreu, Clovis Pompilio de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
Leaf production in three consecutives years of the Calabresa, Fernão Dias and Lopes Lins cultivars of Morus alba was analysed. They were planted at the densities of 6666, 4444 and 3333 plants por hectar (in the spacings of 1.50 x 1.00 m, 1,50 x 1.50 m and 1.50 x 2.00 m, respectively, per plant) and were submitted to three pruning operations during the year. At each pruning the stems were out very low almost at soil surface. Calabresa cultivar fave the highest leaf yields at the density of 6666 plants per hectar find July revealed to be the highest yielding pruning season. The Lopes Lins cultivar gave the lowest yields.